Assessing Civic Participation Around the World: How Evaluations of Journalists' Performance Leads to News Use and Civic Participation Across 22 Countries. (July 2018) - Gil de Zúñiga, Homero; Diehl, Trevor; Ardèvol-Abreu, Alberto
Very little is known about public perceptions of journalists outside Europe and the United States. Even less is known about the role of these attitudes in sustaining civic life around the world. Using individual and country-level survey data, this study explores public attitudes of press performance and their relationship with news consumption and civic participation in 22 countries. The study argues that the nature of civic and local participatory behaviors is often intertwined with notions about what is "good journalism." Results suggest that public evaluations of press performance influence news use. News consumption is also tightly related to civic participation, even in markedly divergent cultural contexts. Citizens' assessment of journalism practice is also a positive moderator of these relationships. This study builds on international comparative work related to the effects of press freedom and journalism practice on stimulating public life.